Western Polemic Writings about Muhammad’s Prophethood - Al-Olaqi, Fahd Mohammed Taleb (Advances in Social Sciences Research Journal, 2016)
This research examines those distorted polemics and outright dubieties about Prophet Muhammad in the Western writings. The anti-Islamic polemical practice was universal. Many more examples of similar polemic biographies can be found in numerous texts of the medieval and early modem period. The Western attitudes to Prophet Muhammad failed to establish sound theoretic basis. The denial phenomenon is the strength in their argument. The Western and Christian polemics on Islamic issues disgrace Islam and its Prophet. It is only new attitudes to research depend clearly on the intentions of the researchers. The modern Western trends work on the history of Prophet Muhammad by avoiding any fabricated accounts while preserving the traditional denial attitude. The study identifies the recurring themes of deception, misinformation and misrepresentation, and confusion in the Western library.